Efficient Engineering Data Exchange in Multi-disciplinary Systems Engineering - Biffl, Stefan; Lüder, Arndt; Rinker, Felix; Waltersdorfer, Laura (Advanced Information Systems Engineering, 2019)
In the parallel engineering of industrial production systems, domain experts from several disciplines need to exchange data efficiently to prevent the divergence of local engineering models. However, the data synchronization is hard (a) as it may be unclear what data consumers need and (b) due to the heterogeneity of local engineering artifacts. In this paper, we introduce use cases and a process for efficient Engineering Data Exchange (EDEx) that guides the definition and semantic mapping of data elements for exchange and facilitates the frequent synchronization between domain experts. We identify main elements of an EDEx information system to automate the EDEx process. We evaluate the effectiveness and effort of the EDEx process and concepts in a feasibility case study with requirements and data from real-world use cases at a large production system engineering company. The domain experts found the EDEx process more effective and the EDEx operation more efficient than the traditional point-to-point process, and providing insight for advanced analyses.